“DEVONU LUG‘OTIT-TURK” ASARIDAGI TURKIY XALQLAR FOLKLORI VA UNING ADABIYOT O‘QITISH METODIKASIDAGI O‘RNI - Yusupov, A.A.; Avezbayeva, J.M. (SCIENCE and SOCIETY, 2025)
The article explains with examples the great importance of “Devonu lug‘otit turk” in terms of studying the history of Turkic peoples and the inclusion of examples of Turkic folklore in this work. Examples of proverbs taken from the work “Devonu lug‘otit turk” are given with explanations.